Persistent Pain Prevalence and Medical Management - Eldon Tunks (Pain Research and Management)
In this issue, Moulin et al (pages 179-184) report an epidemiological survey of persistent pain and medical treatment of this pain in Canada. Two thousand twelve adult Canadians were included in a randomized sample and were interviewed by telephone. The sample was stratified to correspond to the Canadian population's prevalences of sex, age and region, according to the 1996 census data. For this study, the Canadian Ipsos-Reid Express Omnibus survey was used.